1989
DOI: 10.1071/rd9890117
|View full text |Cite
|
Sign up to set email alerts
|

Lupins and energy-yielding nutrients in ewes. II. Responses in ovulation rate in ewes to increased availability of glucose, acetate and amino acids

Abstract: An experiment, using a total of 320 Merino ewes, over two successive breeding seasons was conducted to investigate the separate effects of energy-yielding and protein-yielding nutrients on ovulation rate in sheep. The available energy-yielding or protein-yielding nutrients in the blood of sheep fed a maintenance pelleted ration were increased by either intravenous infusions of metabolites (acetate, glucose or acetate + glucose), feeding lupin grain, modification of the pattern of rumen fermentation to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 0 publications
2
22
0
2
Order By: Relevance
“…For example, in cattle selected for high milk production, high negative energy balance in the post-partum period is associated with reduced fertility (Wathes et al 2007). In sheep, it is well known that an increase in availability of energy substrates is associated with an increase in prolificacy (Teleni et al 1989). In pigs, it is also known that a negative energy balance and a decrease in body fat results in a reduction in litter size and viability of piglets (Quesnel et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in cattle selected for high milk production, high negative energy balance in the post-partum period is associated with reduced fertility (Wathes et al 2007). In sheep, it is well known that an increase in availability of energy substrates is associated with an increase in prolificacy (Teleni et al 1989). In pigs, it is also known that a negative energy balance and a decrease in body fat results in a reduction in litter size and viability of piglets (Quesnel et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, a supplementation for 4-6 days around timing of preovulatory follicle selection increases the ovulation rate over 20-30%, without changes in body weight (Scaramuzzi et al 2006). This effect, termed 'immediate nutrient effect' or 'acute effect', was firstly described to be obtained by supplementing with lupin grains ('lupin effect'; Stewart & Oldham 1986, Teleni et al 1989. Thereafter, numerous studies have reported the positive energy balance of short-term nutritional protocols with energy-yielding nutrients, such as lupin grain (Rowe & Ferguson 1986, Smith & Stewart 1990, Pearse et al 1994, Williams et al 2001, Munoz-Gutierrez et al 2002, corn grain (Landau et al 1995, Letelier et al 2008, infusion of nutrients, like amino acids and glucose (Teleni et al 1989, Downing et al 1995, Landau et al 1996, Rodríguez-Iglesias et al 1996, Rubio et al 1997, Munoz-Gutierrez et al 2002 and metabolic hormones (insulin; Hinch & Roelofs 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its being a precursor of 85% of the lactose exported in milk (Annison and Linzell, 1964), glucose has been shown to be involved in determining ovulation rate (Teleni et al, 1989). Glucose is the main substrate for provision of energy to the uterus and fetuses (Wolff and Meschia, 1982).…”
Section: Introductionmentioning
confidence: 99%